2016
DOI: 10.4137/mbi.s38517
|View full text |Cite
|
Sign up to set email alerts
|

Development of Candida-Specific Real-Time PCR Assays for the Detection and Identification of Eight Medically Important Candida Species

Abstract: Culture-based identification methods have been the gold standard for the diagnosis of fungal infection. Currently, molecular technologies such as real-time PCR assays with short turnaround time can provide desirable alternatives for the rapid detection of Candida microbes. However, most of the published PCR primer sets are not Candida specific and likely to amplify DNA from common environmental contaminants, such as Aspergillus microbes. In this study, we designed pan-Candida primer sets based on the ribosomal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 19 publications
3
40
0
2
Order By: Relevance
“…20 copies/reaction, which corresponds approximately to one-fifth of a single CFU, considering approximately 110 copies of the sequence/CFU (diploid genome) 8 . Other authors who used C albicans culture samples in qPCR observed similar results 14,15 . 7 11.89 ± 0.77 10 5 11.02 ± 0.30 10 7 17.54 ± 0.84 * mean of ten assays; ** mean of three assays; *** mean of five assays; ND -non detected…”
Section: Resultssupporting
confidence: 59%
“…20 copies/reaction, which corresponds approximately to one-fifth of a single CFU, considering approximately 110 copies of the sequence/CFU (diploid genome) 8 . Other authors who used C albicans culture samples in qPCR observed similar results 14,15 . 7 11.89 ± 0.77 10 5 11.02 ± 0.30 10 7 17.54 ± 0.84 * mean of ten assays; ** mean of three assays; *** mean of five assays; ND -non detected…”
Section: Resultssupporting
confidence: 59%
“…The other method is a nested PCR involving a first round of amplification with pan-Candida primers followed by real-time PCR amplification with 8 different species-specific primer pairs for the identification of 8 different Candida species including C. albicans and C. dubliniensis [36]. The additional requirement of the nested step in this procedure [36] is time-consuming, increases cost and the possibility of false-positive results due to amplicon carry-over. Our real-time PCR assay involves only one round of amplification and the method can also be used as a thermal PCR assay with detection of amplicons by agarose gels (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…0.5 ° C) or negligible which may lead to misidentification of some isolates since ITS region sequences vary among clinical C. albicans and C. dubliniensis isolates [5,7,31]. The other method is a nested PCR involving a first round of amplification with pan-Candida primers followed by real-time PCR amplification with 8 different species-specific primer pairs for the identification of 8 different Candida species including C. albicans and C. dubliniensis [36]. The additional requirement of the nested step in this procedure [36] is time-consuming, increases cost and the possibility of false-positive results due to amplicon carry-over.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…; Susever and Yegenoglu ; Zhang et al . ). Alternatively, the use of functional genes (DNA topoisomerase II and phospholipase B gene) for detection of C. tropicalis are also reported (Kanbe et al .…”
Section: Introductionmentioning
confidence: 97%